PENGARUH PENDEKATAN DEEP LEARNING BERBANTU GAMES BAMBOOZLE TERHADAP KEMAMPUAN MENERAPKAN (C3) DAN MINAT BELAJAR SISWA SEKOLAH DASAR KELAS 4 MATA PELAJARAN PENDIDIKAN PANCASILA - Ferdina Aristya Putri; Endra Priawasana; Fauzan Adhim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low ability of elementary school students to apply (C3) the values of Pancasila and their low interest in learning, which is caused by conventional, rote-oriented teaching methods and a lack of innovative media. This study aims to examine the effect of the Deep Learning approach assisted by Baamboozle educational games on the ability to apply concepts (C3) and the learning interest of fourth-grade students in Pancasila Education. This research employed a quantitative approach with a quasi-experimental method using a Pretest-Posttest Control Group Design. The research subjects consisted of 29 students in the experimental group (SDN Wirolegi 04) and 22 students in the control group (SDN Wirolegi 03). Data were collected through contextual essay tests to measure C3 ability and Likert-scale questionnaires for learning interest. Data analysis was performed using the Independent Samples t-test. The results showed that there was a significant influence of the Deep Learning approach assisted by Baamboozle on both variables, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. The experimental group achieved a higher posttest mean score for C3 ability (85.52) compared to the control group (77.64). Furthermore, the effect size analysis using Cohen’s d indicated a very large category of influence. It can be concluded that the integration of the Deep Learning approach and Baamboozle media effectively improves students' cognitive application skills and learning interest, making it a relevant solution for innovative learning in elementary schools.